Respostas
respondido por:
11
3x - 2y = 12
2x + 3y = -5
3x - 2y = 12 (*3)
2x + 3y = -5 (*2)
9x - 6y = 36
4x + 6y = -10
13x= 26
x = 26/13
x = 2
2x + 3y = -5
2*2 + 3y = -5
3y = -5 -4
y = -9/3
y = -3
Resp.:
x*y
2*(-3)
-6
2x + 3y = -5
3x - 2y = 12 (*3)
2x + 3y = -5 (*2)
9x - 6y = 36
4x + 6y = -10
13x= 26
x = 26/13
x = 2
2x + 3y = -5
2*2 + 3y = -5
3y = -5 -4
y = -9/3
y = -3
Resp.:
x*y
2*(-3)
-6
respondido por:
1
Resposta:
3x - 2y = 12
2x + 3y = -5
3x - 2y = 12 (*3)
2x + 3y = -5 (*2)
9x - 6y = 36
4x + 6y = -10
13x= 26
x = 26/13
x = 2
2x + 3y = -5
2*2 + 3y = -5
3y = -5 -4
y = -9/3
y = -3
Resp.:
x*y
2*(-3)
-6
Explicação passo a passo:
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás